A novel de novo mutation p.Ala428Asp in KRT5 gene as a cause of localized epidermolysis bullosa simplex. Issue 10 (20th May 2019) - Stawczyk‐Macieja, Marta; Wertheim‐Tysarowska, Katarzyna; Jakubowski, Rafał; Szczerkowska‐Dobosz, Aneta; Krygier, Magdalena; Wilkowska, Aleksandra; Sawicka, Justyna; Nowak, Wiesław; Bal, Jerzy; Nowicki, Roman
Abstract: Epidermolysis bullosa is a group of inherited blistering skin diseases resulting in most cases from missense mutations in KRT5 and KRT14 genes encoding the basal epidermal keratins 5 and 14. Here, we present a patient diagnosed with a localized subtype of epidermolysis bullosa simplex caused by a heterozygous mutation p.Ala428Asp in the KRT5 gene, that has not been previously identified. Moreover, a bioinformatic analysis of the novel mutation was performed, showing changes in the interaction network between the proteins. Identification of novel mutations and genotype‐phenotype correlations allow to better understanding of underlying pathophysiologic bases and is important for genetic counselling, patients' management, and disease course prediction.